Regression Studies of Binary Complexes of Quinol with Transition Metal Ions in Natural Media - Shaikh Abdul Rahim (International Journal of Scientific Research in Science and Technology, 2025)
The study deals with interaction between chosen transition metal ions with Quinol in aqueous media at temperature 27O C pH metrically by Irving Rossoti method. NaNO3 was used for maintaining ionic strength. Metal to ligand ratio was kept as 1:1. Economical and easily available reagents NaNO3 and HNO3 were used during the work. pKa and logK values and order of stability are evaluated. Data obtained was subjected to regression analysis to find out the relationship between the stability values and physical properties of metal ions. Two physical properties ionisation potential and electronegativity showed regression coeficcient in the range of 0.5. rest of the propeties shoewd no significant corrrelation.
Keywords: Quinol; Regression; Binary Complexes; Transition Metal ions